Helminths of the white ibis, Eudocimus albus (Aves: Therskiornithidae) in Mexico. - Ortega-Olivares, Mirza P.; Hernández-Mena, David I.; de León, Gerardo Pérez-Ponce; García-Varela, Martín (Zootaxa, 2011)
Eight species of helminths are reported from the intestine of 52 white ibis [(Eudocimus albus (Linneaeus)] collected in 14 localities along the Mexican coasts of the Gulf of Mexico, and the Pacific Ocean. Three trematodes, Parastrigea cincta Brandes, 1888; Parastrigea diovadena Dubois & Macko, 1972, and Patagifer lamothei Dronen & Blend, 2008, one cestode Cyclustera ibisae Schmidt & Bush, 1972 and four acanthocephalan species Hexaglandula corynosoma Travassos, 1915, Arhythmorhynchus frassoni Molin, 1858, Southwellina hispida Van Cleave, 1925, Ibirhynchus dimorpha GarcíaVarela, Pérez-Ponce de León, Aznar & Nadler, 2011, were found. Four of these species were recorded for the first time in the white ibis, raising the number of helminth species that parasitize this bird to 57 along its distributional range. Additionally, 4 of the helminth species are recorded in Mexico for the first time.